Lærarar, målfolk og namnerenessanse - Kruken, Kristoffer (NAMN OG NEMNE, 2020)
School teachers and (other) adherents of the Nynorsk language movement have usually been considered a leading group in the Nordic name renaissance at the end of the 19th century. In a previous article (2018b) I called that point of view in question because these groups did not stand out in the coinage of new Nordic names of Old Norse character. However, the conclusions did not fully convince me, so I have made a new investigation based on the censuses of 1900 and 1910 in combination with a wide range of biographical literature. The new material confirms the traditional point of view. Furthermore, it shows that the teachers in the eastern and northern parts of the Âcountry are far ahead of the teachers in the western parts. This geografical pattern has not previously come to light. Generally, teachers and other people who adhere to the Nynorsk movement use more Old Norse names than the rest of the society. In many cases the name renaissance is modified by traditional naming after members of the Âfamily.